Seasonal and habitat effects on the nutritional properties of savanna vegetation: Potential implications for early hominin dietary ecology. Issue 133 (August 2019) - Paine, Oliver C.C.; Koppa, Abigale; Henry, Amanda G.; Leichliter, Jennifer N.; Codron, Daryl; Codron, Jacqueline; Lambert, Joanna E.; Sponheimer, Matt
Abstract: The African savannas that many early hominins occupied likely experienced stark seasonality and contained mosaic habitats (i.e., combinations of woodlands, wetlands, grasslands, etc.). Most would agree that the bulk of dietary calories obtained by taxa such as Australopithecus and Paranthropus came from the consumption of vegetation growing across these landscapes. It is also likely that many early hominins were selective feeders that consumed particular plants/plant parts (e.g., leaves, fruit, storage organs) depending on the habitat and season within which they were foraging. Thus, improving our understanding of how the nutritional properties of potential hominin plant foods growing in modern African savanna ecosystems respond to season and vary by habitat will improve our ability to model early hominin dietary behavior. Here, we present nutritional analyses (crude protein and acid detergent fiber) of plants growing in eastern and southern African savanna habitats across both wet and dry seasons. We find that many assumptions about savanna vegetation are warranted. For instance, plants growing in our woodland habitats have higher average protein/fiber ratios than those growing in our wetland and grassland transects. However, we find that the effects of season and habitat are complex, an example being the unexpectedly higher protein levels we observe in the grasses and sedges growing in our Amboseli wetlands during the dry season. Also, we find significant differences between the vegetation growing in our eastern and southern African field sites, particularly among plants using the C4 photosynthetic pathway. This may have implications for the differences we see between the stable carbon isotope compositions and dental microwear patterns of eastern and southern African Paranthropus species, despite their shared, highly derived craniodental anatomy.